Conjugation of methotrexate to poly(L-lysine) increases drug transport and overcomes drug resistance in cultured cells - Ryser, Hugues J.-P. (1978)
Methotrexate and [(3)H]methotrexate were conjugated through a carbodiimide-catalyzed reaction to a 70,000 molecular weight poly(L-lysine) in molar ratios of approximately 13 to 1. The cellular uptake of labeled conjugate was far in excess of the uptake of free drug in cells that were either proficient or deficient in methotrexate transport. The conjugate markedly inhibited the growth of PRO(-)3 Mtx(RII) 5-3 Chinese hamster ovary cells, which are known to be drug resistant by virtue of a deficient methotrexate transport. The cells, however, were not inhibited by the same concentrations of free poly(Lys) and free drug. The 100-fold difference in drug concentration needed to inhibit the mutant cells and their corresponding wild type was totally abolished by exposing the methotrexate-resistant cells to methotrexate-poly(Lys). That the drug is carried into the resistant cells as intact drug-poly(Lys) is evident also from the fact that the conjugate is rendered inactive by brief trypsinization in vitro. Because the conjugate fails to inhibit dihydrofolate reductase (5,6,7,8-tetrahydrofolate: NADP(+) oxidoreductase; EC 1.5.1.3) in vitro, it must be concluded that the strong growth inhibitory effect of the conjugate is due to the intracellular hydrolysis of its polymeric backbone, followed by the release inside the cell of a pharmacologically active form of methotrexate. Our date show that in methotrexate-resistant cells the intracellular release of active drug after uptake of conjugate is of the same order of magnitude as the uptake of free drug by transport-proficient cells and, hence, that the drug resistance due to deficient transport can be totally overcome.